GLOBAL REPORTING PRINCIPLES OF REPORTING NON-FINANCIAL INFORMATION - Altun, Nihal (Bursa Teknik Üniversitesi, 2018)
The developments and changes that took place in the past century have brought about changes in the functions and methods of businesses. Assets are more sustainable when existing businesses offer collecting plus value to create economic value. For this reason, many institutions and organizations are engaged in social responsibility, sustainability activities and present their activities to the stakeholders. Corporate social responsibility, which is of great importance for society and stakeholders, presents how sustainability reports perform, and contains future plans and projects. The aim of this study is to explain the concept of enterprise reporting, its scope, the development process and the framework of global sustainability reporting principles and to draw a general framework with the relevant literature

Geçtiğimiz yüzyılda yaşanan gelişmeler ve değişimler işletmelerin işlevleri ve yönetimleri konusunda değişiklik meydana getirmiştir. Ekonomik değer yaratmak için var olan işletmeler topluma artı değer sundukları zaman varlıkları daha sürdürülebilir olmaktadır. Bu nedenle birçok kurum ve kuruluş sosyal sorumluluk, sürdürülebilirlik faaliyetlerinde bulunmakta ve faaliyetlerini paydaşlarının bilgisine sunmaktadırlar. Toplum ve paydaşlar açısından büyük önem arz eden kurumsal sosyal sorumluluk, sürdürülebilirlik raporları kurumların nasıl performans gösterdiklerini sunmakta ve gelecek ile ilgili plan ve projelerini barındırmaktadır. Bu çalışmanın amacı kurumsal raporlama kavramını, kapsamını, gelişim sürecini ve küresel sürdürülebilirlik raporlama ilkelerinin çerçevesini açıklamak ve ilgili literatür ile genel bir çerçeve çizmektir
FİNANSAL OLMAYAN BİLGİLERİN RAPORLANMASINDA KÜRESEL RAPORLAMA İLKELERİ